Vitamina D, adiponectina e alterações do sono nos estados de resistência à insulina - Oliveira, Roseane Feitosa de (2016)
Endocrine-metabolic disorders (EMD) are frequent and associated with severe comorbidities and mortality. Chronics leep restriction relates to EMD and potentially aggravates health problems including EMD. Vitamin D is important for organ functions and adiponectin is essential for the regulation of lipid metabolism. This study evaluates clinical characteristics of patients with EMD and risk factors in connection with vitamin D and adiponectin levels. The objectives were to investigate the profile of EMD patients regarding vitamin D status and risk factors associated with vitamin D abnormalities and to examine clinical characteristics of EMD patients with insufficient sleep, and risk factors associated with adiponectin levels. This is a cross-sectional investigation of patients with EMD from the Centro Integrado de Hipertensão e Diabetes, consecutively recruited in the period of 2010-2011. Vitamin D and adiponectin levels were determined. Insufficient sleep, characterized as habitual <6h of sleep, was identified. Physical exercise status was investigated. Two-hundred-fifty patients aged 29-82 years (58.2±11.3), 58.4% female were studied. Arterial hypertension (AH, 76.4%), type 2 diabetes (T2D, 79.2%) and glucose intolerance (13.2%) were present. Overweight (42.8%) and obesity (43.6%) were common. Among AH patients, 59.7% were women and mostly in menopause (87.7%). Most patients with AH also had T2D (79.6). Individuals with Vitamin D insufficiency/deficiency had higher diastolic pressure. Patients with Vitamin D insufficiency/deficiency showed a commensurate increase of gamma glutamyl transpherase (GGT, p=0.005). Multiple logistic regression analysis showed that menopause, T2D, arterial hypertension and reduced exercise were independently associated with lower levels of vitamin D. In another study, 332 patients (18 to 80 y) with EMD underwent clinical evaluation, and adiponetin levels were determined. Older age and increased adiponectin levels were associated with reduced hours of sleep. The association between insufficient sleep and adiponectin levels was maintained after adjusting for gender, age, menopause, BMI, arterial hypertension, ADA classification and physical exercise level (p=0.001). In conclusion, patients with arterial hypertension, T2D, menopause and sedentary life style are at high risk of vitamin D insufficiency/deficiency. Individuals with EMD that have Vitamin D insufficiency/deficiency present higher levels of GGT and potentially more liver toxicity. Insufficient sleep is common in patients with EMD. High adiponectin levels are independently associated with insufficient sleep. A compensatory mechanism may explain the latter findings.